ANALISIS PERBANDINGAN TRADING VOLUME ACTIVITY DAN ABNORMAL RETURN SAHAM SEBELUM DAN SESUDAH STOCK SPLIT (STUDI KASUS PADA PERUSAHAAN YANG TERDAFTAR DI BEI) - Tanto, Tanto (MABIS, 2013)
The very high raise of stock will cause the decrease in demand of it. A policy which can be used by company to avoid that risk is to do stock split. Stock split is expected to be able to increase the stock liquidity and to give positive signal to investor that the company is in a well condition. The research about stock split has been conducted many times and it gave various results. This research is intended to re-picturize one of the form of corporate action which is stock split and the impact to Trading Volume Activity and Stock Abnormal Return. This research was done on 15 companies which are registered in BEI during the period of 2008 â2010. The research method used Descriptive Statistics Research Method on EventStudy. The Statistics Analysis that used was t-test during ten days of event window whichÂ consisted of 5 days before and 5 days after stock split and also 60 days estimation periodÂ from t-65 to t-5. TÂ Â arithmetic of t-test for Trading Volume Activity average during the periodbefore and after stock split with tÂ Â table = 2,262 is 3,594, so tarithmetic> ttable and the conclusion isHo is rejected, which means the average of Stocks Trading Volume Activity in BEI differsÂ significantly between the period before and after the stock split. Meanwhile tÂ Â arithmetic of t-testfor Stocks Abnormal Return between the period before and after the stock split with tÂ Â table=2,262 is 0,959 so tÂ Â arithmetic< ttable and the conclusion is Ho is accepted, which means the averageof Stocks Abnormal Return in BEI doesnt differ significantly between the period before andÂ after the stock split.Â Â